City of joy [videorecording (DVD)] - Joffé, Roland, 1945-; Joffé, Roland, 1945-; Swayze, Patrick; Collins, Pauline, 1940-; Puri, Om; Malik, Art; Lapierre, Dominique (Columbia TriStar Home Entertainment, 2004)
An American doctor, a British nurse and an illiterate Indian farmer join together to transform a Calcutta ghetto when it is threatened by the brutal local "godfather."